Fate, source and mass budget of sedimentary microplastics in the Bohai Sea and the Yellow Sea. (1st February 2022) - Zhang, Mingyu; Lin, Yan; Booth, Andy M.; Song, Xikun; Cui, Yaozong; Xia, Bin; Gu, Zhangjie; Li, Yifan; Liu, Fengjiao; Cai, Minggang
Abstract: As reservoirs for pollutants transported via the Yangtze and Yellow Rivers, the Bohai Sea (BS) and Yellow Sea (YS) play an important role in transporting microplastics (MPs) to the Pacific Ocean. The fate, sources and mass budget of MPs in the BS and the YS were investigated by Pearson correlation, principal component analysis-multilinear regression analysis (PCA-MRLA) and a mass balance model to sedimentary MPs data. Average MP abundances were 137 and 119 items kg −1 in the Bohai and Yellow Seas, respectively. MPs <1000 μm exhibited similar distribution patterns to total organic carbon and fine-grained sediments, while MPs >1000 μm were confined in the BS and exhibited a strong positive correlation with chlorophyll-a and polyethylene terephthalate, suggesting that larger MPs might deposit faster due to biofouling or when comprised of high density polymers. PCA-MLRA analysis indicated land-based inputs (packing materials, textile material and daily commodities) were dominant in the BS, while maritime activities (fishing and mariculture) were the main source of MPs in the YS. The mass balance model revealed that the total MP input and output to the BS and the YS was 3396.92 t yr −1 and 3814.81 t yr −1, respectively. The major input pathway of MPs to the BS and the YS were river discharge and air deposition, respectively. Notably, 94% of MPs in the BS and the YS were deposited to sediments. This study revealed that BS and YS sediments play an important role in preventing MPs from being further transported to the Pacific Ocean, thus more attention should be paid to local ecological risk assessment. Graphical abstract: Image 1 Highlights: Small-sized MPs show similar transportation mechanisms as TOC and fine-grain sediment. Large-sized MPs sinking mechanisms are influenced by large surface area and density. Land-based origins exceed maritime origins by 54% of total microplastics. A box balance model revealed sedimentation accounted for 94% of the total output.